DEVELOPING OF A TEXTBOOK BASED ON THE LOCAL WISDOM IN KABUPATEN JEPARA FOR GRADE V ELEMENTARY SCHOOL STUDENTS - Zaenal Arifin; Sri Utaminingsih; Gunawan Setiadi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study aimed to: (1) develop thematic textbooks based on local wisdom for the materials about Our Best Friend's Environment for grade V elementary school students and (2) know the validity, practicality, and effectiveness of thematic textbooks based on local wisdom for the materials about Our Best Friend's Environment for grade V elementary school students. This textbook was developed by using Research and Development (R & D) method. The development stages included: (1) Potentials and problems, (2) Data collection, (3) Product designs, (4) Design validations, (5) Design revisions, (6) Product testings, and (7) Product revisions (Sugiyono, 2016). This study was conducted to 33 students from class V SDN 2 Sendang Kabupaten Jepara. The initial product development was a process of making media based on needs analysis. Expert testings or validation was carried out by 2 experts, namely media experts and material experts. The data in this study were collected through observations, interviews, and questionnaires. Then, the data were analyzed by using descriptive analysis and comparison test of two independent groups, namely by using the independent t-test. Based on the results of the trial, this thematic textbook was very valid, very interesting, effective, and could be applied in learning. This could be seen from the results of the validation by three experts showing that the product was good. Moreover, the results of the effectiveness test showed that students at the experimental class had better learning outcomes than those in the control class. This means that the textbook based on local wisdom in Kabupaten Jepara were developed effectively.